2, 4‐dichlorophenol induces ER stress‐mediated apoptosis via eIF2α dephosphorylation in vitro. Issue 2 (27th August 2014) - Zhang, Xiaoning; Zhang, Xiaona; Qi, Yongmei; Huang, Dejun; Zhang, Yingmei
ABSTRACT: 2, 4‐Dichlorophenol (2, 4‐DCP) has been widely used to produce herbicides and pharmaceutical intermediates, which exhibits various toxic effects including apoptosis. However, the mechanisms underlying 2, 4‐DCP‐induced apoptosis, especially mediated by endoplasmic reticulum (ER) stress, are still unknown. In the present study, the mouse embryonic fibroblasts (MEFs) were used as an in vitro model system to figure out whether 2, 4‐DCP could induce ER stress, and further to elucidate the role of ER stress in 2, 4‐DCP‐induced apoptosis. The results showed that 2, 4‐DCP dramatically caused the decrease of cell viability, the increase of apoptotic cells, the collapse of mitochondrial membrane potential (MMP) and the activation of caspase‐3, suggesting that 2, 4‐DCP did induce apoptosis. Meanwhile, 2, 4‐DCP acted similarly as ER stress agonist tunicamycin (Tu) to activate all three branches (IRE1α, ATF6 and eIF2α) of ER stress. Furthermore, repression of ER stress or inhibition of eIF2α dephosphorylation significantly alleviated 2, 4‐DCP‐induced apoptosis. Taking these results together, the present study firstly showed that 2, 4‐DCP induced ER stress‐mediated apoptosis via eIF2α dephosphorylation in mammalian cells. These findings will provide new insights into the mechanisms underlying apoptosis after chlorophenols exposure. © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 245–255, 2016.